Prevalence, Risk Factors, and Clinical Outcomes of Cardiac Complications in Patients with Type 2 Diabetes Mellitus. A Clinic-Based Observational Study - Muhammad Sameer Hanif, Syed Asjad Ur Rehman Omer, Gul E Nasreen, Asghar Ali Memon, Mumtaz Lakho, Muhammad Qasim (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The risk of cardiovascular complications is significantly increased in Type 2 Diabetes Mellitus (T2DM) and is still the major cause of morbidity and mortality in the diabetic population. There are limited outpatient-based data in Pakistan to quantify this burden and to identify associated risk factors in a routine clinical setting. The study was to find out the prevalence, risk factors, and clinical outcomes of cardiac complications in T2DM patients attending tertiary care hospitals. Methods: It was a cross-sectional observational study done at Mayo Hospital Lahore and Abwa Medical College Faisalabad from May 2022 to May 2023. A total of n=120 patients 35 years and older with confirmed T2DM were recruited. Lab tests, clinical histories, and cardiovascular assessments, including electrocardiography and echocardiography, were done. Cardiac complications considered were: ischemic heart disease, left ventricular hypertrophy, congestive heart failure, and diabetic cardiomyopathy. SPSS v26.0 was used to analyze the data with statistical significance at p < 0.05. Results: In 64 patients (53.3%), cardiac complications were found. The most common was LVH (23.3%), followed by IHD (20.8%), CHF (7.5%), and diabetic cardiomyopathy (1.7%). Duration of diabetes >10 years (p = 0.003), hypertension (p = 0.001), poor glycemic control (HbA1c >8%) (p = 0.004), and dyslipidemia (p = 0.009) were associated with significance. During the study period, two patients (1.7%) died of cardiac events. Conclusion: T2DM patients are commonly affected by cardiac complications. Cardiovascular screening is recommended as routine in those with poor metabolic control and comorbidities to prevent adverse outcomes. Outpatient care of the diabetic should prioritize integrated cardiac assessment. Keywords: Type 2 Diabetes Mellitus, cardiac complications, hypertension, glycemic control, Pakistan.